Titanitas de granitos paleoroterozoicos reduzidos e oxidados, Província Carajás: um estudo morfológico e composicional por MEV/EDS - REIS, Yuri Harrison da Costa (2022)
Titanites are common accessory minerals in oxidized metaluminous granites, and rare in reduced peraluminous granites. Titanites crystals incorporate in its structure a wide variety of major, minor elements and geologically important features (Al, Fe, Sn, Nb, Ta, W, Ce, Y) capable of providing information about their formation conditions and the metallogenetic potential of their host rock. These facts contribute to the importance attributed to the present study. Paleoproterozoic A type granites, such as Serra da Queimada and Bom Jardim, belonging to the Velho Guilherme Intrusive Suit, occur in the vicinity of São Félix do Xingu, in the south-central of the state of Pará, in the Carajás Mineral Province. Both present reduced character and present Sn and W mineralizations in their more evolved and hydrothermal facies and in associated greisens bodies. They consist of biotite syenogranites and monzogranites. The absence, or very limited occurrence, of magnetite and primary titanite and the presence of ilmenite indicate that these granites belong to the Ilmenite series. Paleoproterozoic Bannach and Redenção A type granites, located immediately south of the Bannach and Redenção cities, SE of Pará, have oxidized character and are inserted in the Jamon Suite; monzogranites predominate with syenogranites occurring subordinately; the presence of magnetite as the main opaque mineral makes it possible to include them in the magnetite series. In the reduced Bom Jardim granite, only secondary titanites from the alteration of ilmenite and chlorite were identified. In the Serra da Queimada reduced granite are locally present primary titanite crystals associated with amphibole and biotite, in addition to secondary titanites from chlorite alteration. In the Bannach and Redenção oxidized granites, titanites are primary and associated with amphibole and biotite crystals. The titanites of the reduced granites, both primary and secondary, presented higher levels of Sn + W + Ta + Nb + Ce and lower Y compared to the primary titanites of oxidized granites. This study showed that titanites of reduced (mineralized) and oxidized (sterile) granite have different geochemical signatures and can be used preliminarily as indicators of this type of mineralization. The identification and morphological and geochemical characterization of different types of titanites present in these rocks will complement the studies carried out so far in the Bom Jardim, Serra da Queimada, Bannach and Redenção granites.